2005
DOI: 10.1001/archpedi.159.3.261
|View full text |Cite
|
Sign up to set email alerts
|

Acculturation as a Predictor of the Onset of Sexual Intercourse Among Hispanic and White Teens

Abstract: Low acculturation emerges as a significant protective factor while controlling for other social and cultural factors, in spite of the increased risk of initiating sexual intercourse for Hispanic teens overall. Hispanic Spanish speakers were least likely to have initiated intercourse, while Hispanic English speakers were the most likely.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
44
0

Year Published

2005
2005
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 67 publications
(47 citation statements)
references
References 17 publications
(17 reference statements)
3
44
0
Order By: Relevance
“…[10,16,[20][21][22] English predominance has also been linked to recent condom use [21] and higher risk of adolescent pregnancy [22]. In addition, one analysis of school-based data from the National Longitudinal Study of Adolescent Health that examined the combined effects of language and time spent in the U.S. [10], found that U.S.-born youth or youth residing in the U.S. for 12 or more years, who also lived in English-speaking homes, were more likely to be sexually experienced than those in Spanish-speaking homes.…”
Section: Languagementioning
confidence: 99%
“…[10,16,[20][21][22] English predominance has also been linked to recent condom use [21] and higher risk of adolescent pregnancy [22]. In addition, one analysis of school-based data from the National Longitudinal Study of Adolescent Health that examined the combined effects of language and time spent in the U.S. [10], found that U.S.-born youth or youth residing in the U.S. for 12 or more years, who also lived in English-speaking homes, were more likely to be sexually experienced than those in Spanish-speaking homes.…”
Section: Languagementioning
confidence: 99%
“…However, more acculturated Latino youth may engage more frequently in high-risk behaviors, such as drug use (Adam et al 2005;Epstein et al 1998), which may increase their likelihood of exposure to violence.…”
Section: Introductionmentioning
confidence: 99%
“…Use of English language has previously functioned well as a proxy for acculturation for Latinos of MexicanAmerican background (Cuellar and Gonzalez 1996;Marin and Gamba 1996), and other studies of health behaviors have used self-reported language usage as a measure of acculturation (Adam et al 2005;Epstein et al 1998;Yu et al 2003). Based on previous research, we hypothesized that those youth with greater fluency in English would report greater violence exposure (Adam et al 2005;Epstein et al 1998) and that students with lower fluency would have greater expression of PTSD symptoms in the avoidance PTSD symptom cluster, which has been found in Mexican samples (Norris et al 2001), and less functional impairment, especially in the academic domain (Kao 1999).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Behaviors contributing to the above pattern of outcomes among Latino youth include earlier onset of sexual activity (Adam et al, 2005;Ford & Norris, 1996;Gilliam et al, 2007), greater likelihood of having multiple sexual partners Doherty et al, 2007;Ford & Norris, 1996), and lower rates of consistent condom use (Brady et al, 2009b;Gurman & Borzekowski, 2004;Kim et al, 2007). Earlier efforts to reduce these risky behaviors among Latino youth emphasized the need for culturally relevant prevention programming (Afable-Munsuz & Brindis, 2006;Deardorff et al, 2010;Herbst et al, 2007) focusing on strengthening individual psychosocial characteristics (Villarruel et al, 2004), and familial (Lescano et al, 2009) or relationship dynamics (Brown et al, 2008;Tschann et al, 2010) associated with lower rates of sexual risk behaviors.…”
mentioning
confidence: 99%